BANGLADESH FROM ARISE TO INDEPENDENCE - Tariq Najm Abdul Wahid, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Bangladesh was subordinate to Pakistan, but its inhabitants were suffering from marginalization and exclusion before they attained complete independence. This provoked the population against the ruling Pakistani authorities, so the population launched a comprehensive revolution led by Mujibur Rahman, during which the revolutionaries demanded full independence from Pakistan. Pakistan refused this, which led to overall battles in the areas of Bengal. Thousands of people fled to neighboring India to get rid of the ongoing battles between the two sides, and thus India had to bear the burdens of these fleeing population to their countries.So that Pakistan demanded to stop the military operations against Bengal. But the Pakistani authorities did not. It responded, which led to India entering the war on the side of the population of Bangladesh, and this matter ultimately led to the victory of the India Front, the declaration of the independence of Bangladesh and the recognition of that independence by the Pakistani authorities.